2023
DOI: 10.1108/lht-10-2022-0468
|View full text |Cite
|
Sign up to set email alerts
|

User experience of digital science and education evaluation platform: identification and analysis of key influencing factors

Abstract: PurposeEstablishing and developing digital science and education evaluation platforms (DSEEPs) have several practical implications for the development of China's science, technology and education. Identifying and analyzing the key factors influencing DSEEP user experience (UX) can improve the users' willingness to use the platform and effectively promote its sustainable development.Design/methodology/approachFirst, a literature survey, a five-element model of UX and semi-structured interviews were used in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…User experience, digital marketing tactics, and e-commerce platform convergence have all been found to be important variables affecting these businesses' competitiveness and market reach. Research has indicated that e-commerce firms' competitiveness is significantly impacted by characteristics including customer happiness (Lakra et al, 2022), a variety of information forms and comprehensive information content (Qiu et al, 2023), and service level and customer satisfaction (Minh & Hiep, 2023). Furthermore, it has been discovered that improving the user experience by focusing on elements like interface design, interaction design, and user interface (Gahlot & Rani, 2023;Hu, 2022) increases users' propensity to use digital science and education assessment platforms.…”
Section: Introductionmentioning
confidence: 99%
“…User experience, digital marketing tactics, and e-commerce platform convergence have all been found to be important variables affecting these businesses' competitiveness and market reach. Research has indicated that e-commerce firms' competitiveness is significantly impacted by characteristics including customer happiness (Lakra et al, 2022), a variety of information forms and comprehensive information content (Qiu et al, 2023), and service level and customer satisfaction (Minh & Hiep, 2023). Furthermore, it has been discovered that improving the user experience by focusing on elements like interface design, interaction design, and user interface (Gahlot & Rani, 2023;Hu, 2022) increases users' propensity to use digital science and education assessment platforms.…”
Section: Introductionmentioning
confidence: 99%